Postfaktisches Erzählen? Post-Truth − Fake News − Narration - Chihaia, Matei; Martínez, Matías; Rennhak, Katharina; Scheffel, Michael; Sommer, Roy; Weixler, Antonius (spectrum Literaturwissenschaft / spectrum Literature, 2021)
It is often claimed in contemporary public debate that we live in a "post-factual age." This interdisciplinary volume employs the theories and methods of narrative research to investigate the relationship between the "post-factual" and narrative. It seeks to make sense of the core concepts in the debate, such as post-factual, post-truth, reality and truth, events, tales, stories, and narratives.